Consanguinity by random isonymy and socioeconomic development in Argentina: a population study - Dipierri, Jose Edgardo (2016)
In human populations various flexible, labile and interdependent structures (genetic, demographic, socioeconomic) co-exist, each of which can be organized in an hierarchical order corresponding to administrative entities. The relationship between consanguinity, as estimated by random isonymy (F ST), and socioeconomic conditions was analysed at different levels of political and administrative organization in Argentina. From the surnames of 22,666,139 voters from the 2001 electoral roll, F ST was estimated for 510 Argentinian departments. Using a principal component analysis, a Socio-Demographic and Economic Indicator (SDEI), summarizing the effect of 22 socioeconomic and demographic variables at the departmental level, was computed. The relationship between departmental F ST and SDEI values was analysed for the whole nation and within regions using multiple regression analysis. The F ST presented a clinal distribution with the highest values in the north and west of the country, while SDEI expressed the opposite behaviour. A negative and significant correlation was observed between F ST and SDEI, accounting for 46% of the variation in consanguinity in Argentina. The strongest correlations of F ST with SDEI were observed in the Central, Patagonia and Cuyo regions, i.e. those with the highest values of SDEI and lowest values of F ST.